A magnetically-induced Coulomb gap in graphene due to electron-electron interactions - Evgenii E. Vdovin; Mark T. Greenaway; Yurii N. Khanin; Sergey V. Morozov; Oleg Makarovsky; Amalia Patanè; Artem Mishchenko; Sergey Slizovskiy; Vladimir I. Fal’ko; Andre K. Geim; Kostya S. Novoselov; Laurence Eaves (Communications Physics, 2023)
Abstract Insights into the fundamental properties of graphene’s Dirac-Weyl fermions have emerged from studies of electron tunnelling transistors in which an atomically thin layer of hexagonal boron nitride (hBN) is sandwiched between two layers of high purity graphene. Here, we show that when a single defect is present within the hBN tunnel barrier, it can inject electrons into the graphene layers and its sharply defined energy level acts as a high resolution spectroscopic probe of electron-electron interactions in graphene. We report a magnetic field dependent suppression of the tunnel current flowing through a single defect below temperatures of ~2 K. This is attributed to the formation of a magnetically-induced Coulomb gap in the spectral density of electrons tunnelling into graphene due to electron-electron interactions.